Basic methods of cryptography - Lubbe, Jan C. A. (Cambridge University Press, 1998)
This text covers the fundamentals of cryptography, the means of establishiing security in the storage and transportation of information. With the proliferation of computer use in business, information is being communicated and processed automatically on a large scale. Medical and financial files, automatic banking, video-phones, pay-tv, facsimiles, tele-shopping, and global computer networks all process highly sensitive information.